Sleepyhead - Smee, Nicola (Pan Macmillan, 2001)
This book presents a little rhyme for bedtime. Ten tired fingers, ten tired toes . . . Two tired eyelids, one tired nose.Each brightly illustrated picture book in this series has a clever rhyming text that Mom or Dad will enjoy sharing with baby when it's time for play or sleep. An added bonus is a surprise touch-and-feel page at the back of each book. The final illustration in this book is embellished with a textured material that toddlers will want to touch. It feels just like baby's bedtime blanket.
Keywords: Concepts; General; Juvenile Fiction